Silicon photonic MEMS switches based on split waveguide crossings - Yinpeng Hu; Yi Sun; Ye Lu; Huan Li; Liu Liu; Yaocheng Shi; Daoxin Dai (Nature Communications)
Abstract The continuous push for high-performance photonic switches is one of the most crucial premises for the sustainable scaling of programmable and reconfigurable photonic circuits for a wide spectrum of applications. Conventional optical switches rely on the perturbative mechanisms of mode coupling or mode interference, resulting in inherent bottlenecks in their switching performance concerning size, power consumption and bandwidth. Here we propose and realize a silicon photonic 2×2 elementary switch based on a split waveguide crossing (SWX) consisting of two halves. The propagation direction of the incident light is manipulated to implement the OFF/ON states by splitting/combining the two halves of the SWX, showing excellent performance with low excess loss and low crosstalk over an ultrawide bandwidth. Both elementary switch and a 64×64 switch array based on Benes topology are fabricated and characterized, demonstrating great potential for practical scenarios such as photonic interconnect/routing, Lidar and spectroscopy, photonic computing, as well as microwave photonics.